Transition management for organic agriculture under citrus cultivation favors fungal diversity in soil - Scotton, Juliana Cristina [UNESP]; Homma, Sergio Kenji; Costa, Wesley Luiz Fialho; Pinto, Diego Fontebasso Pelizari; Govone, Jose Silvio [UNESP]; Attili-Angelis, Derlene [UNESP] (Cambridge Univ Press, 2020)
The present international scenario recognizes organic agriculture as an innovative solution to reduce agrochemicals and practices that degrade the agroecosystem. Yet, the shift from an already well-established agricultural model to a relatively new one is a challenging task and requires further scientific support. This work investigated the influence of transitional management - TM (from conventional to organic agriculture) on the soil fungal community under citrus, in dry and rainy periods. From 2012 to 2015 on, an area in Mogi Guacu, SP, Brazil was selected, and two treatments were installed: a conventional management (CM) system based on farming practices with agrochemicals and fertilizers use, and another, transition management (TM) based on a 25% reduction per year of the chemical substances used in CM, with soil conditioner bokashi introduced. The performance of the transition system was evaluated in the context of soil fertility and diversity index of fungal taxa, by plate culture isolation, through the richness of Margalef (D-mg), diversity of Shannon (H ') and reverse Simpson (D). Differences in the occurrence and frequency ofPaecilomyces,greater under CM andPenicillium, greater under TM, highlighted the influence of the management system employed. Richness and diversity indices were higher under TM. Principal component analysis revealed that 49.9% of the differences in fungal diversity was due to the management system. Only 16.5% was a result of the season of sampling. Four years of reduction/replacement of chemical practices in TM was sufficient to modify and favor some soil fungal taxa and consequently their activity. This research brings promising results to organic agriculture initiatives with relevant results for a tropical climate area.
Keywords: citrus; Paecilomycesspp; soil fungi; sustainable agriculture; transition management